PERBEDAAN SKALA KEKUATAN OTOT SEBELUM DAN SESUDAH LATIHAN MENGGENGGAM PADA PENDERITA CEREBRO VASCULAR DISEASES (CVD) - Daeli, Novita Elisabeth; Suwarno, Maria Lousiana; Budiharto, Budiharto (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2018)
Cerebro vascular diseases (CVD) also known as stroke is the event losing of brain function that is caused by the termination of blood supply to the brain. The deprivation of oxygen supply will result in depleting nutrition to the brain. The primary symptom will be the muscle weakness. The muscle weakness on hand can be treated with a grasp exercise for the post-stroke patient. This researched aims to understand the difference of muscle strength scale before and after grasp exercising for the post ischemic stroke patient. The research design applies quasi-experiment with pretest and posttest on two groups design. In this research, there are 67 respondents will be used as samples by applying purposive sampling technique. The research instrument is observation paper of the muscles strength scale. The bivariate analysis uses paired t-test with significance level ?(0.05). The  result of this research indicates a significant difference in the muscle strength scale before and after the exercise on ischemic stroke patient with the score p<0,0001. In conclusion, this research finds that the grasp exercise can effectively increase the muscle strength of the stroke patient and recommends the grasp exercise as a part of nurse independent intervention in providing nursing treatment. Keywords: Stroke, muscle strength, grasp exercise.